2014
DOI: 10.12980/apjtb.4.201414b66
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of renal dysfunction by nutraceuticals prepared from oil rich plant foods

Abstract: Administration of the studied nutraceuticals proved to possess protective role against cisplatin-induced nephrotoxicity, chromosomal aberration and abnormal sperms. All studied nutraceuticals showed complete safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…Natural products of plant origin (nutraceuticals) have been proposed as a potential source of natural antioxidants with pharmaceutical activity ( 9 - 11 ). Also the therapeutic effects of nutraceuticals for curing kidney dysfunction are being studied ( 12 ). Elevated oxidative stress and reduced antioxidant defense systems in patients with diabetes and ESRD accelerate the prevalence of chronic complications such as hemolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Natural products of plant origin (nutraceuticals) have been proposed as a potential source of natural antioxidants with pharmaceutical activity ( 9 - 11 ). Also the therapeutic effects of nutraceuticals for curing kidney dysfunction are being studied ( 12 ). Elevated oxidative stress and reduced antioxidant defense systems in patients with diabetes and ESRD accelerate the prevalence of chronic complications such as hemolysis.…”
Section: Introductionmentioning
confidence: 99%
“…β-Sitosterol, which is the main compound showing neurite outgrowth-promoting activity in sunflower seed extract, is one of the well-known plant sterols and is found in avocados, soybeans and corn [ 32 , 33 ]. It was reported that β-sitosterol has cholesterol metabolic action, antibacterial action and anticancer action [ 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…ALA also reduces serum triglycerides and the development of thrombosis and arteriosclerosis (Pszczola, 1998). Also, flaxseed was shown to have an impact on the treatment of lupus nephritis (Clark et al, 1995) in humans and improvement of renal dysfunction during cisplatin treatment in rats (Al-Okbi et al, 2014), pointing to its reno-protective effect. Flaxseed oil attenuated the decline in renal function and reduced glomerular injury (Caligiuri et al, 2013).…”
Section: Discussionmentioning
confidence: 99%